RAMADAN AND THE STRENGTHENING OF SOCIAL COHESION: A STUDY OF LOCAL WISDOM IN MULTICULTURAL SOCIETIES - Hartati, C. Dewi; Wirawati, Sri Mukti; Fahmi, Ahmad Rosikhul; Gymnastiar, Iman Ahmad; Manggala, Kayan (GoAcademica CRP, 2025)
This study aims to examine the role of Ramadan in strengthening social cohesion through the lens of local wisdom within multicultural societies using a systematic literature review approach. By analyzing existing literature sourced primarily from reputable international databases, including Scopus and Web of Science, this research identifies significant themes concerning the relationship between Ramadan practices and social harmony. The findings indicate that Ramadan significantly contributes to enhancing social integration and mutual understanding among diverse cultural and religious groups. Local wisdom embedded within Ramadan traditions, such as communal iftars, charity distributions, and interfaith dialogues, facilitates meaningful interactions and reinforces collective solidarity. Moreover, the literature highlights variations in how different multicultural communities interpret and enact local wisdom, underscoring both unique adaptations and commonalities that strengthen social ties. The review also reveals challenges, including societal tensions and differing religious interpretations, which sometimes complicate the cohesion process. However, Ramadan's overarching emphasis on compassion, generosity, and inclusivity remains a powerful catalyst for social bonding. Policymakers and community leaders can utilize these insights to formulate strategies aimed at promoting harmonious coexistence in increasingly diverse societies. Despite extensive discussions, this literature-based analysis recognizes the limitations inherent in the secondary nature of the data, suggesting the need for empirical studies to deepen understanding further. Ultimately, this review contributes to existing scholarship by illuminating how culturally contextualized Ramadan observances can effectively foster sustainable social cohesion in multicultural contexts.